Krisen, Umbrüche und Revolutionen Rahmenthema 1 für das Abitur 2013 - Austermann, Lambert; Bethlehem, Siegfried; Bratvogel, Friedrich W.; Gawatz, Andreas; Goldmann, Justus; Henselmeyer, Ulrich; Lahme, Jörg; Lendzian, Hans-Jürgen; Ringelsbacher, Beatrix; Schlegel, Claus; Schütze, Friedhelm; Norden, Jörg van (Zeiten und Menschen, 2011)
Wahlpflichtmodul: Die Weltwirtschaft in der Krise